إمكانية التوليف بين الأقمشة المتنوعة والكروشية في عمل منتجات ملبسية - الدسوقي، هبة عاصم أحمد; أحمد، أسماء حسن علي; حسن، غادة رفعت أحمد (الجمعية العلمية للمصممين, 2019)
The process of mixing raw materials has become an essential feature that enriches the clothing materials. Objective: The present research attempts to offer a range of innovative garments embellished with Crochet. The research problem: has been to identify how to improve the aesthetics of clothing products offered as evening clothes for women aged 18-30 years. The main objective of the research was to establish new and innovative ways to integrate the crochet with women's evening clothes using the Jasmine stitch. Methods: The research sought to achieve this by studying the properties of materials and threads identified in the research and also the possibility of integrating them in women's evening clothes. Hypothesis: The study hypothesized that there are statistically significant differences between the proposed designs. There are statistically significant differences between the proposed designs in the extent of achieving design elements. There are statistically significant differences between the proposed designs in the extent of achievement of the functional side. The results of the research were found to have significant statistical differences between the responses of the arbitrators on the proposed designs in achieving the foundations of the design. The value of (P) was 270.97 at the significance level (0.001) There are significant differences between the responses of the arbitrators on the designs proposed in the achievement of design elements. The value of (P) 130.80 at the level of significance (0.001), indicating the differences between the designs in this pillar, there are significant differences The results showed that there were differences between the designs in this pillar. The most used designs for the elements and the foundations of the design and the functional side of the design according to the opinions Arbitrators.
أصبح ظاهرة توليف الخامات سمة أساسية تثري الخامات. يحاول البحث الحالي تقديم مجموعة من المنتجات الملبسية المبتكرة والمطعمة بالكروشية. تتحدد مشكلة البحث في التعرف على كيفية الارتقاء بالجانب الجمالي في المنتجات الملبسية المقدمة كملابس سهرة للسيدات من الفئة العمر (18-30سنة)، كان أهم أهداف البحث هو البحث عن أساليب جديدة ومبتكرة لدمج الكروشية مع ملابس السهرة للسيدات باستخدام غرزة الياسمينة. وسعى البحث لتحقيق هذا من خلال دراسة خصائص الخامات والخيوط المحددة بالبحث ومدى إمكانية توظيفهم معاً في ملابس السهرة للسيدات. وتم في الدراسة تصميم 40 موديل لملابس السهرة للسيدات، وافترض البحث وجود فروق دالة إحصائياً بين التصميمات المقترحة في مدى تحقيق أسس التصميم، وتوجد فروق دالة إحصائياً بين التصميمات المقترحة في مدى تحقيق عناصر التصميم، وتوجد فروق دالة إحصائياً بين التصميمات المقترحة في مدى تحقيق الجانب الوظيفي للتصميم، منهج البحث: استخدمت الدراسة المنهج الوصفي التحليلي والمنهج التجريبي، نتائج البحث توجد فروق ذات دلالة إحصائية بين استجابات السادة المحكمين على التصميمات المقترحة في تحقيق أسس التصميم حيث بلغت قيمة (ف) 270.97 عند مستوى الدلالة (0.001) مما يدل على وجود فروق بين التصميمات في هذا المحور، توجد فروق ذات دلالة إحصائية بين استجابات السادة المحكمين على التصميمات المقترحة في تحقيق عناصر التصميم حيث بلغت قيمة (ف) 130.80 عند مستوى الدلالة (0.001) مما يدل على وجود فروق بين التصميمات في هذا المحور، توجد فروق ذات دلالة إحصائية بين استجابات السادة المحكمين على التصميمات المقترحة في تحقيق الجانب الوظيفي للتصميم حيث بلغت قيمة (ف) 185.25 عند مستوى الدلالة (0.001) مما يدل على وجود فروق بين التصميمات في هذا المحور، حيث حصلت التصميمات الأكثر توظيفاً لعناصر وأسس التصميم والجانب الوظيفي للتصميم وفقاً لآراء المحكمين.
Keywords: إنتاج الملابس -- توليف الخامات -- الكروشية -- ملابس النساء